Next-Gen DNS and Security Challenges in IoT Ecosystems - Anasuri, Sunil (International Journal of Emerging Research in Engineering and Technology, 2022)
The meteoric growth of Internet of Things (IoT) has transformed the networking sector by connecting billions of heterogeneous devices to the Net. The benefits created by this digital revolution are unprecedented in relation to automation, monitoring, and decision making. Nevertheless, it also brings significant security flaws as well as questions of scalability, especially across legacy Domain Name System (DNS) infrastructure. DNS is a very important Internet component, which translates human-readable names into IP addresses that can be understood by machine. As the number of IoT devices grows, the question of supporting performance, security, and reliability of traditional DNS becomes difficult. DNS-based attack supports such as cache poisoning, DDoS, DNS tunnelling, and spoofing are easy to launch against IoT devices, since IoT devices often have weak security capabilities, at least by comparison with a PC or other managed device. Moreover, these problems are complicated by the fact that, unlike with popular protocols (HTTP, HTTPS, FTP, TCP), the tools used in IoT are not standardized, thus compounding the problem of adaptation to DNS. The paper explores the future forms of DNS, improvements on security protocols like DNSSEC and DNS over HTTPS (DoH) and DNS over TLS (DoT), and decentralized one like blockchain based DNS. It nulls their contributions in alleviating the security challenges that are IoT-specific, low latency, and facilitating the ability of IoT networks to handle massive scales. The paper encompasses an elaborate literature review, test methodology to assay the resilience of security, and performance tracking in the emulated IoT conditions. Lastly, it suggests an inclusive security mechanism that consists of edge computing, AI-based pattern detection, and safe DNS setup to facilitate future IoT infrastructure